A comparative study of continuous versus interrupted suturing for repair of episiotomy or second degree perineal tear - Jena, Lopamudra; Kanungo, Shyama (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study has been taken up to assess the effects of continuous versus interrupted suturing methods on the incidence of short and long term postpartum maternal morbidity experienced by women following repair of episiotomy or second-degree perineal tears after vaginal birth. Methods: This comparative prospective study was conducted in department of obstetrics and gynaecology of S.C.B. medical college, Cuttack, Odisha to compare continuous suturing technique with interrupted method for the repair of episiotomy and second degree perineal tear following vaginal delivery in 211 women. One group was repaired with continuous non-locking sutures involving the vaginal mucosa, perineal muscles and subcutaneous tissue for skin and other group had continuous locking stitch of vaginal mucosa, interrupted sutures in perineal muscles and interrupted transcutaneous stitches for skin. Identical suture material (catgut supplied by the government) was used for both the groups. The mothers were interviewed on the 2nd, 10th and 42nd day following repair regarding pain perception with lying, walking and sitting posture using Visual Analogue Scale (VAS). Results: The pain score measured by VAS on 2nd day showed mild to moderate pain in continuous group compared to moderate and severe pain in interrupted group (P = 0.008) in lying position and (P = 0.000) in sitting and walking position. On 10th day no difference in perception in lying position (P = 0.571) but more subjects of interrupted group had pain in sitting and walking position (P = 0.05). On 42nd day no difference in pain perception in both groups was seen (P = 1.000). There was no difference in wound dehiscence in both the groups (P = 0.361). Subjects in the interrupted group had greater complains of dyspareunia compared to subjects in continuous group (P = 0.009). Less length of suture were required in the continuous group (P = 0.000). Conclusions: Continuous suturing technique for repair of episiotomy and second degree of perineal tear compared to interrupted methods are associated with less short term pain, dyspareunia and amount of suture material used is also less but there is no difference in daily work after 42 days and incidence of wound dehiscence.